Parkinson's disease affects the neural alpha oscillations associated with speech‐in‐noise processing - De Groote, Evelien; Eqlimi, Ehsan; Bockstael, Annelies; Botteldooren, Dick; Santens, Patrick; De Letter, Miet (The European journal of neuroscience, 2021)
Parkinson's disease (PD) has increasingly been associated with auditory dysfunction, including alterations regarding the control of auditory information processing. Although these alterations may interfere with the processing of speech in degraded listening conditions, behavioural studies have generally found preserved speech‐in‐noise recognition in PD. However, behavioural speech audiometry does not capture the neurophysiological mechanisms supporting speech‐in‐noise processing. Therefore, the aim of this study was to investigate the neural oscillatory mechanisms associated with speech‐in‐noise processing in PD. Twelve persons with PD and 12 age‐ and gender‐matched healthy controls (HCs) were included in this study. Persons with PD were studied in the medication off condition. All subjects underwent an audiometric screening and performed a sentence‐in‐noise recognition task under simultaneous electroencephalography (EEG) recording. Behavioural speech recognition scores and self‐reported ratings of effort, performance, and motivation were collected. Time‐frequency analysis of EEG data revealed no significant difference between persons with PD and HCs regarding delta‐theta (2–8 Hz) inter‐trial phase coherence to noise and sentence onset. In contrast, significantly increased alpha (8–12 Hz) power was found in persons with PD compared with HCs during the sentence‐in‐noise recognition task. Behaviourally, persons with PD demonstrated significantly decreased speech recognition scores, whereas no significant differences were found regarding effort, performance, and motivation ratings. These results suggest that persons with PD allocate more cognitive resources to support speech‐in‐noise processing. The interpretation of this finding is discussed in the context of a top‐down mediated compensation mechanism for inefficient filtering and degradation of auditory input in PD. Persons with Parkinson's disease (PD) demonstrated decreased speech recognition scores and increased alpha power during a sentence‐in‐noise recognition task compared with healthy controls (HCs). These results suggest that persons with PD allocate more cognitive resources to support speech‐in‐noise processing, possibly reflecting a top‐down mediated compensation mechanism for inefficient filtering and degradation of auditory input in PD.